Pengaruh Produksi Dan Omzet Penjualan Terhadap Pendapatan Pengerajin Tenun Di Desa Peringgesela - Laeli, Baiq (Alpatih Harapan Semesta, 2023)
The purpose of this study was to determine the effect of production and sales turnover on weaving craftsmen income in peringgesela vilage of 2019-2020. The design of this study was descriptive quantitative. The sampling technique used in this study was probably sampling with a random sampling of 166 respondents. The result of this study found that the variable production has a positive or significant effect on income, the value was 2.503 > 2.001, which meant that it was accepted. The sales turnover variable has a positive or significant effect income, the value was 2.070 > 2.001, which a meant that it was accepted. Simultaneously, the variable production and sales turnover on income have a positive effect which the value of 7.467 > 3.153 was obtained. From the results of the Wilcoxon production variable test, sales turnover on income has a significant effect of more than 0.05, which meant that there was a difference before (2019) and during Covid-19 (2020). The positive impact for the variable was obtained before Covid-19 which was 4.9344, while during Covid-19, it was 5.0328 because craftsmen were more productive in producing goods. Furthermore, the negative impact was craftsmen got the reductions of sales turnover and income because of the social distancing, so that foreign people cannot visit.